Analisis Pengaruh Pengangguran dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Provinsi Sumatra Barat Tahun 2019-2023 - Gun Pernanda, Celfin; Zia Ulhak, Mhd (Bertuah Jurnal Syariah dan Ekonomi Islam, 2023)
This study aims to assess the extent to which unemployment rates and economic growth influence poverty levels in West Sumatra Province during the 2019–2023 period. Utilizing multiple linear regression analysis and secondary data from the Central Statistics Agency, the study revealed that unemployment rates have a positive and significant impact on poverty. Conversely, economic growth also contributes to rising poverty levels, indicating that such growth is not inclusive. These findings highlight the importance of fostering inclusive economic growth and reducing unemployment rates as key strategies to alleviate poverty in the region.